Optimalisasi Pemanfaatan Tanaman Obat Keluarga Melalui Pembuatan TOGA Spot dan Pengelolaan Produk Olahan di Desa Pace - Nurcholis, Mahfud; Safira, Firdina Dea; Gusman, Cahya Sefty; Jannah, Nur Akhillah Roikhatul; Tatiana, Septin Amelia Putri; Nabila, Alifatun; Yuliana, Diah Trisna; Aliansyah, Fery Ardi; Fitriani, Irmaliya Nova; Wafiy, Nizar Nur; Prasetiyo, Prasetiyo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The Program Mahasiswa Berdesa (Promahadesa) DESENTRAL is carried out in Pace Village, Silo District, Jember Regency which is one of the villages supported by Jember University. The village community utilizes their land for ginger cultivation, making it the largest ginger-producing area in Jember Regency. This is evidenced by data from the BPS Jember Regency in 2023. In addition to ginger, there are other types of medicinal plants (TOGA) such as turmeric, galangal, and other plants. There is an issue where the utilization of TOGA plants is not yet optimal, as they are considered household medicinal plants and not utilized as a source of health or business opportunities. Given the lack of innovation in processing herbal products, which are sold in their raw form without being processed into value-added products, the Promahadesa DESENTRAL team adopted a participatory and applied approach focused on utilizing the assets and potential of Pace Village. The participatory and applied approach is implemented through five main stages: focus group discussions (FGD), education, field demonstrations, skill training, monitoring, and evaluation. Activities will focus on planting TOGA and training in processing harvests into instant ginger, instant turmeric, and ginger gummy. TOGA planting will be conducted on village hall land with various plant species totaling 50 seedlings. Processing training will be conducted with the community using demonstration and hands-on methods to produce instant ginger, instant turmeric, and ginger gummy. Through this activity, TOGA plants will be monitored by the local community and the harvest will be processed into instant ginger, instant turmeric, and ginger gummy that are ready to sell so as to provide added economic value to the village community. The results of training, packaging, and marketing have been effective with the community participation rate reaching 95% and the satisfaction evaluation shows a “very good” category.